Does capital marketization promote better rural industrial integration: evidence from China - Ding, Zhao; Fan, Xinyi (Frontiers in Sustainable Food Systems, 2024)
Although rural industrial integration is a crucial pathway for advancing the revitalization of rural economies, it continues to grapple with financial challenges. This paper delves into the theoretical underpinnings of how capital marketization influences rural industrial integration. Using panel data from China's provinces spanning the years 2010 to 2020, a comprehensive index of rural industrial integration is constructed from the vantage point of a new development paradigm. The paper employs the system GMM method to empirically investigate the impact of capital marketization on rural industrial integration and to dissect its transmission mechanisms. Additionally, a threshold regression model is applied to explore the specific patterns of the nonlinear relationship between the two variables. The findings reveal that the influence of capital marketization on rural industrial integration follows a "U-shaped" trend. Rural financial development and the structure of industries are identified as two pivotal transmission channels for the effects of capital marketization. In Addition, the study uncovers a dual threshold effect in the impact of capital marketization.